A Targumist interprets the Thora: contradictions and coherence in Targum Pseudo-Jonathan - Zhakevich, Iosif J. (Supplement to Aramaic studies, 2022)
This book conducts a study of contradictions and coherence in Targum Pseudo-Jonathan and suggests that the alleged contradictions are ultimately given to resolution, once the greater context of biblical and Jewish tradition is taken into consideration.